Pendampingan Penyusunan Standard Operational Procedure (SOP) dan Desain Kemasan bagi IKM Makanan di Kabupaten Kediri dan Kota Batu - Abdul Kodir; Muh Ariffudin Islam; Galih Wahyu Pradana; Trias Madanika Kusumaningrum; Khoirur Rozaq (Universitas Negeri Surabaya, 2020)
Batu and Kediri City are areas in East Java with very high tourism potential. The creativity of business actors seizes this opportunity with the many emerging SMIs engaged in processed food/beverages which are commonly used by tourists for souvenirs. To create a good food company, it requires a good application of SOP and attractive product packaging and in accordance with the Indonesian National Standard. The purpose of this activity is to provide training in the preparation of Standard Operational Procedure (SOP) and design product packaging in the processed food/beverage business in Batu City and Kediri. The training and mentoring method is used to achieve the goal of increasing the competitiveness of the Food Small and Medium Industries (IKM) in Batu City and Kediri City. The training participants were 50 processed food and beverage businesses that had potential but had constraints on the preparation of SOPs and product packaging that had not been maximized. The results of this training showed a change in the behavior of participants, initially, only 10% of participants in Kediri and 6.7% in Batu had an SOP to 100%. Furthermore, participants who did not design their packaging properly in Kediri were 66.7% and in Batu 70% higher the results had increased to 100%. These results indicate that the participants experienced an increase in their ability to prepare SOPs and design packaging.